2015
DOI: 10.1088/0004-637x/812/1/17
|View full text |Cite
|
Sign up to set email alerts
|

The Arrowhead Mini-Supercluster of Galaxies

Abstract: Superclusters of galaxies can be defined kinematically from local evaluations of the velocity shear tensor. The location where the smallest eigenvalue of the shear is positive and maximal defines the center of a basin of attraction. Velocity and density fields are reconstructed with Wiener Filter techniques. Local velocities due to the density field in a restricted region can be separated from external tidal flows, permitting the identification of boundaries separating inward flows toward a basin of attraction… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 18 publications
1
26
0
Order By: Relevance
“…Jaaniste et al (1998) have noted the flatness of this supercluster; this supercluster is also aligned almost perpendicular to the line of sight. The authors assumed that the flatness of this supercluster is enhanced and we see the effect of the matter inflow towards the supercluster axis, in accordance to what we observe in the nearby space for the Laniakea and Arrowheads superclusters (Tully et al 2014;Pomarède et al 2015).…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Jaaniste et al (1998) have noted the flatness of this supercluster; this supercluster is also aligned almost perpendicular to the line of sight. The authors assumed that the flatness of this supercluster is enhanced and we see the effect of the matter inflow towards the supercluster axis, in accordance to what we observe in the nearby space for the Laniakea and Arrowheads superclusters (Tully et al 2014;Pomarède et al 2015).…”
Section: Introductionsupporting
confidence: 91%
“…Numerical simulations show that the positions of the high-density peaks in the galaxy distribution in the early Universe are fixed by the processes during or just after the inflation and do not change much during the cosmic evolution, only the amplitude of over-and underdensities grows with time (Kofman & Shandarin 1988;Bond et al 1996;van de Weygaert & Schaap 2009;Suhhonenko et al 2011, and references therein). Observational data of the movements of galaxies in the nearby Laniakea and Arrowhead superclusters show that galaxy velocities are directed towards supercluster axis (Tully et al 2014;Pomarède et al 2015), and galaxies are moving from underdense regions towards high-density regions. This process may accelerate the collapse of individual cores, but it is unlikely that the cores will approach each other and merge.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Filaments running from the vicinity of the NGC 5353/4 group to the Virgo (e.g., Canes Venatici filament, see the gray rectangle in Fig. 3a) and Coma clusters in different SGY ranges have been reported in the past (Tully & Trentham 2008;Pomarède et al 2015), but the NGC5353/4 filament identified here is not specifically referred to in previous studies.…”
Section: Data and Analysismentioning
confidence: 75%
“…Turning attention to the Hercules Void, dominant structures on the back side are the Great Wall at SGY∼ +7000 km s −1 (de Lapparent et al 1986) merging into the Hercules complex at SGZ∼ +7000 km s −1 (Bahcall & Soneira 1984) and further merging into the Ophiuchus (Johnston et al 1981) and Libra+8 structures at SGX∼ −6000 kms. On the near side, the over densities are the less consequential Local Supercluster, creating a separation from the Local Void, and such other minor features as the Hydra−Cancer filament and the Arrowhead mini-supercluster (Pomarède et al 2015). Above the supergalactic equator (SGZ> 0) essentially everywhere locally densities are below the mean.…”
Section: Morphology Of the Wallsmentioning
confidence: 99%